Evaluation of rural transportation technology: a case study of bicycle and motorcycle trailers - Oyesiku, Olukayode O.; Akinyemi, Olasunkanmi O.; Giwa, Solomon O.; Lawal, Nurudeen S.; Adetifa, Babatunde O. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Transportation of goods in rural communities, especially from farms, is one of the major bottlenecks experienced by rural dwellers. Bicycle and motorcycle trailers have been a major intervention proposed by several studies but, this technology has not been fully adopted and it has no detailed evaluation report. This study, therefore, evaluates the performance of different bicycle and motorcycle trailer designs. Three different designs of bicycle trailers (fixed plate design (FPD), convertible plate design (CPD) and wire mesh design (WMD)) and two designs of motorcycle trailers (FPD and CPD) were developed. Four performance evaluation tests (laden mass, forward speed, pull and haulage tests and a computer-based simulation of stress/strain analysis) were carried out. The optimum load capacity (OLC) of WMD bicycle trailer is 100 kg at a speed of 5.2 – 6.3 km/hr, while that of FPD and CPD bicycle trailers are 100 kg at a speed of 3.8 - 4.2 km/hr. The OLC for the FPD and CPD motorcycle trailer was 200 kg at a speed of 6.2 – 8.4 km/hr. Static structural analysis of the trailer chassis shows that the maximum stress and strain of the trailers were 2.95 × 106 Pa and 8.22 × 10-6 mm, respectively. This study shows the suitability of the bicycle and motorcycle trailers in small-scale goods conveyance and its suitability for the rural community.